Sleep, Mood, and Nutrition Patterns of Postmenopausal Women Diagnosed with Major Depressive Disorder by Menopause Periods - Cansu Kabadayı Demir; Sinem Bayram; Beril Köse; Esra Köseler Beyaz; Esen Yeşil (Life, 2024)
Menopausal women experience changes in ovarian activity and fluctuating hormone levels. The aim of this study was to detect ongoing sleep and nutritional problems in postmenopausal women. This study was conducted with 62 postmenopausal women who had been diagnosed with major depressive disorder, were aged 42–64, were not dieting for at least 1 month, and had been using antidepressants for at least 6 months. The Pittsburgh Sleep Quality Index and Depression Anxiety Stress Scale–42 were used. Anthropometric measurements were taken and body composition analysis was performed. The prevalence of obesity and overweight were 12.9% and 71%, respectively. Hot flashes, night sweats, and mood swing were more common in those who had been through menopause for <5 years. Also, the PSQI, Depression, and Stress scores of those women were higher. Women who had been menopausal for ≥5 years had a higher BMI, waist/hip ratio, and fat mass and better sleep quality and lower daytime dysfunction according to the PSQI. Energy and fat intake were higher, while protein, vitamin C, and calcium intakes were lower in women who had been menopausal for ≥5 years. It is crucial for healthcare professionals to review approaches for early and late menopausal periods and to individualize treatment options, especially in patients whose symptoms persist.